Analisa Penerapan Kurikulum Individu untuk Kemandirian Siswa ABK di Homeschooling Putragama (HSPG) Yogyakarta - Dirgahayu Ari Astuti (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims: (1) To analyze the individual curriculum planning of Children with Special Needs (ABK) at Homeschooling HSPG Yogyakarta. (2) To analyze the organization of the individual curriculum for Children with Special Needs (ABK) at Homeschooling HSPG Yogyakarta. (3) To analyze the implementation of the individual curriculum for Children with Special Needs (ABK) at Homeschooling HSPG Yogyakarta. (4) To analyze the evaluation of individual curriculum for Children with Special Needs (ABK) at Homeschooling HSPG Yogyakarta. (5) To analyze the obstacles and solutions in curriculum management for individual children with special needs (ABK) at Homeschooling HSPG Yogyakarta. The type of research used in this research is qualitative research, using interview, observation, and documentation techniques. In this study, researchers will explore and find out how to plan, organize, and carry out evaluations, constraints, and solutions in individual curriculum management for the independence of ABK students in Homeschooling Putragama (HSPG) Yogyakarta City. This research was conducted on students with special needs at the Putragama Homeschooling (HSPG) in Yogyakarta City. The analysis used is the analysis of the Miles and Huberman models. Researchers reduce, present, draw conclusions, and verify data. Based on the results of data analysis, the conclusions are obtained: (1) Individual curriculum planning is derived from a national curriculum that is adapted or modified with the ability of ABK. (2) Organizing the regular curriculum into an individual curriculum is carried out by the school curriculum development team. Facilities and infrastructure for ABK at HSPG Yogyakarta can only cover children with mild autistic needs and mild mental retardation. (3) The implementation of learning is carried out by GPK or therapy teachers according to the ability and creativity of the teacher so that students can be enthusiastic about learning. (4) Reports on student evaluation results, both therapy and academic reports, are compiled into formative reports and summative reports. (5) Obstacles in the follow-up assessment to observe student characteristics or behavioral observation data and parental information that was not honest in the initial assessment.